Growing old together: What we know about the influence of diet and exercise on the aging host's gut microbiome - Brooks, Chequita N.; Wight, Madeline E.; Azeez, Oluwatobi E.; Bleich, Rachel M.; Zwetsloot, Kevin A. (Frontiers in Sports and Active Living, 2023)
The immune system is critical in defending against infection from pathogenic microorganisms. Individuals with weakened immune systems, such as the elderly, are more susceptible to infections and developing autoimmune and inflammatory diseases. The gut microbiome contains a plethora of bacteria and other microorganisms, which collectively plays a significant role in immune function and homeostasis. Gut microbiota are considered to be highly influential on host health and immune function. Therefore, dysbiosis of the microbiota could be a major contributor to the elevated incidence of multiple age-related pathologies. While there seems to be a general consensus that the composition of gut microbiota changes with age, very little is known about how diet and exercise might influence the aging microbiome. Here, we examine the current state of the literature regarding alterations to the gut microbiome as hosts age, drawing particular attention to the knowledge gaps in addressing how diet and exercise influence the aging microbiome. Further, we will demonstrate the need for more controlled studies to investigate the roles that diet and exercise play driving the composition, diversity, and function of the microbiome in an aging population.